Natural compounds as therapeutic agents for amyloidogenic diseases - Vassallo, Neville (Advances in Experimental Medicine and Biology, 2015)
This edited volume concerns a group of devastating neurological disorders that share a common pathological mechanism, namely the aggregation and deposition of insoluble, proteinaceous lesions, termed 'amyloid'. Examples of cerebral amyloid disorders include common neurodegenerative diseases like Alzheimer's disease-related dementia and Parkinson's disease, as well as other less prevalent conditions like Huntington's disease, cerebral amyloid angiopathy and the transmissible prion disorders. A disease-modifying therapeutic agent is still lacking for all these diseases, and there are no approved therapies that target amyloid formation directly. Nevertheless, a large and complex group of natural aromatic compounds known as polyphenols are rapidly emerging as potentially potent anti-amyloidogenic agents. This book collectively presents a considerable body of experimental and epidemiological evidence from peer-reviewed scientific publications that support a role for natural compounds and herbal extracts in the chemoprevention and therapy of amyloidogenic disorders. Each contribution is written by scientific experts in the relevant field; chapters are devoted to Mediterranean diet and olive oil phenols, traditional Chinese medicine, herbal extracts, polyphenols (with a particular emphasis on epigallocatechin-3-gallate) and bi-flavonoids, amongst others. The topic of this book is relevant to a wide audience, from academia and university students in the biological and chemical sciences, to physicians and allied health professionals, as well as people working in the nutraceutical industry.